2023
DOI: 10.17576/jkukm-2023-35(1)-10
|View full text |Cite
|
Sign up to set email alerts
|

Review: Magnetic Field Ability to Treat Hydrocarbon Fuel in Internal Combustion Engine

Abstract: The increasing consumption of fossil fuels and the high emission of exhaust gases have encouraged researchers to explore different approaches to reduce its consequences. Apart from focussing on the engine components, modifications on the fuel molecules can also deliver huge improvement. Using magnetic fields on the fuel line becomes one of the promising alternatives to give a better performance of the engine and produce less hazardous emissions. Previous researchers have proven that the magnetic field could en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…It has been observed that magnetic fields increase laminar flame velocity and optimize combustion processes in Calophyllum Inophyllum biodiesel [94]. Additionally, by influencing fuel molecules, magnetic fields can lead to better reactions with oxygen and improved combustion, especially in hydrocarbon fuels [95]. Furthermore, the application of magnetic fields to microalgae cultivation has shown promising results in achieving high-efficiency biomass concentration and accumulating carbohydrates and lipids, making it a viable alternative for third-generation biofuel production [96].…”
Section: Potential Applications Of Magnetic Field To Combustionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been observed that magnetic fields increase laminar flame velocity and optimize combustion processes in Calophyllum Inophyllum biodiesel [94]. Additionally, by influencing fuel molecules, magnetic fields can lead to better reactions with oxygen and improved combustion, especially in hydrocarbon fuels [95]. Furthermore, the application of magnetic fields to microalgae cultivation has shown promising results in achieving high-efficiency biomass concentration and accumulating carbohydrates and lipids, making it a viable alternative for third-generation biofuel production [96].…”
Section: Potential Applications Of Magnetic Field To Combustionmentioning
confidence: 99%
“…Int J Energy Studies 2024; 9(1): 188 It has been found that magnetic fields have various effects on combustion and explosions, leading to potential industrial applications. Firstly, they can enhance fuel efficiency and engine performance by increasing the combustion rate and improving the reaction between fuel and oxygen [95]. Secondly, magnetic fields can reduce emissions by influencing the orientation of hydrocarbons and facilitating the oxidation process [99].…”
Section: Potential Applications Of Magnetic Field To Combustionmentioning
confidence: 99%
See 1 more Smart Citation